Chester treadmill police tests as alternatives to 15-m shuttle running. (13th April 2019) - Morris, M; Deery, E; Sykes, K
Abstract: Background: Police officers require a specific level of aerobic fitness to allow them to complete personal safety training and specialist roles. Officers' aerobic fitness is assessed using the 15-m multi-stage fitness test (MSFT); however, due to the agility required and risk of injury, two alternative treadmill tests have been designed to predict four of the key minimum VO2 criteria of 35, 41, 46 and 51 ml·kg −1 ·min −1 . Aims: To investigate the validity and reliability of Chester Treadmill Police Walk Test (CTPWT) and Chester Treadmill Police Run Test (CTPRT). Methods: Seventy-eight UK police officers (18 females) completed the CTPWT ( n = 53) or CTPRT ( n = 35), or both, generating a total of 88 data sets. To assess reliability, 43 participants returned for a second visit (T2), to repeat the treadmill test. Results: Mean differences between predicted and actual VO2 at 35, 41, 46 and 51 ml·kg −1 ·min −1 were as follows −1.1, −2.1, −0.1 and −1.2 ml·kg −1 ·min −1 . Despite a significant under prediction ( p = 0.001), a minimum of 92% of participants were within 10% of target VO2 at all levels. There was no significant difference between actual and predicted VO2 in the CTPRT, at 46 ml·kg −1 ·min −1 (T1 46.0 ± 1.4 or T2 45.1 ± 1.3 ml·kg −1 ·min −1 ). Similarly, there was no significant difference at 51 ml·kg −1 ·min −1 (T2 50.5 ± 1.4 ml·kg −1 ·min −1 ). We observed no differences for gender or trial. Ninety-five per cent limits of agreement were at worst −0.25 ± 4.0 ml.kg −1 .min −1 between trial 1 and 2. Conclusions: The CTPWT and the CTPRT provide a valid and reliable alternative to the 15-m MSFT.